Bacterial Contamination of Escherichia coli in Long Beans at Traditional Markets - Muhammad Ali Shodikin; Ika Rahmawati Sutejo; Dini Agustina; Angga Mardro Raharjo; Anaditya Wahyu Kumudhaningsih (Jurnal Kesehatan Prima, 2022)
Escherichia coli (E. coli) bacteria may contaminating uncooked food and cause food poisoning disease. Long beans (Vigna sinensis L) is one of the vegetable that consumed by people in raw (uncooked) and often traded in traditional markets. Many traditional markets do not meet sanitation requirements and many sellers do not perform good personal hygiene. These situation can potentially to cause bacterial contamination of vegetables sold in traditional markets. There has been no research examining E. coli contamination in long beans that sold at traditional markets in Jember.The purpose of this study to prove the contamination of E. coli bacteria in long beans at traditional markets in Jember. The research method uses an observational descriptive design with the cross sectional approach. Research places in eight traditional markets in Jember Regency and Microbiology Laboratory, Faculty of Medicine, University of Jember. The samples used amounted to 40 long beans purchased from 40 traditional market traders. The microbiological examination is performed using the most probable number (MPN) method, namely presumptive test and completed test. The results showed from the presumptive test all of 40 samples (100%) contaminated with coliform bacteria. After completed tests, 36 out of 40 samples (90%) were found contaminated by E. coli. The majority of long beans sold in traditional markets have been contaminated by E. coli bacteria.